Utilization of Interactive Digital Teaching Materials in Aqidah Akhlaq Learning at Madrasah Ibtidaiyah - Maulana, Meiviani Nurul Aisyah; Maslani; Maesak, Cantri; Lubis, Asridayani; Taufiqurrahman (Journal of Innovation and Research in Primary Education, 2025)
This study examines the use of interactive digital teaching materials in Aqidah Akhlaq learning at Madrasah Ibtidaiyah (MI) in response to the growing role of Information and Communication Technology (ICT) in education. It aims to describe the implementation of digital materials, analyze teacher and student experiences, and identify supporting factors and challenges. Using a qualitative descriptive approach through literature study, data were gathered via interviews, observation, and documentation involving teachers and students. Results show that digital materials improve student motivation, participation, and understanding of religious concepts. Narrative-based media, such as animated Islamic stories, foster emotional connection and engagement. However, challenges include limited digital infrastructure, gaps in teacher skills, and unequal policy support, especially in non-urban areas. The study concludes that integrating technology in religious education strengthens cognitive, affective, and spiritual development but requires systematic efforts in teacher training, infrastructure, and inclusive policies